Pastoral calasancia: un espacio más significativo para los adolescentes y jóvenes - Montoya Monsalve, Silvia Luz (Educación, 2017)
This article presents the reality that inhabits the pastoral work of the colegio Calasanz in Medellín today, specifically the high school students, where it is has been demonstrating a lack of motivation and lack of connection with classes and each one of the projects that accompany the pastoral. First of all, we will have part of the story where emerging principles and values which are fundamental pedagogía and calasanz spirituality and how it has been doing a way with each of them. Second, we will address the realities that teens and calasancios young people experience and how the pastoral is responding or not to them, on the basis of the same reality expressed by the educational community from focus groups as a research methodology. Third launch proposal giving light to the path of these new generations who increasingly demand a more Christian humanity and a more humane Christian community.